VARIABILITATEA SOMACLONALĂ LA PLANTELE DE TUTUN TRANSGENIC - Duca, Maria; Glijin, Aliona; Lupaşcu, Victor; Orosco-Cardenas, Martha (CEP USM, 2007)
In this paper it was analyzed the somaclonal variation of 13 genetically modified tobacco lines (T1generation), that express the bar gene. It was shown that five lines had greater plant dimensions in comparison to the control ones. Also, in all transgenic tobacco lines there were detected higher accumulation of hydrogen peroxide invascular tissues. All these suggest that observed changes appeared as the result of plant transformation and regeneration at morphological and biochemical levels.
Keywords: variabilitatea somaclonală